2019
DOI: 10.1007/s00401-019-01998-x
|View full text |Cite
|
Sign up to set email alerts
|

FUS pathology in ALS is linked to alterations in multiple ALS-associated proteins and rescued by drugs stimulating autophagy

Abstract: Amyotrophic lateral sclerosis (ALS) is a lethal disease characterized by motor neuron degeneration and associated with aggregation of nuclear RNA-binding proteins (RBPs), including FUS. How FUS aggregation and neurodegeneration are prevented in healthy motor neurons remain critically unanswered questions. Here, we use a combination of ALS patient autopsy tissue and induced pluripotent stem cell-derived neurons to study the effects of FUS mutations on RBP homeostasis. We show that FUS’ tendency to aggregate is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 33 publications
6
87
0
Order By: Relevance
“…One possibility is that different FG-Nups might stabilize the liquid state when combined together. Analogues for this hypothesis are ubiquitous in the literature, e.g., the inhibition of amyloid-β plaques or aggregates by α-synuclein (Bachhuber et al, 2015) or mixing of the intrinsically disordered protein FUS with EWS or TAF15 (Marrone et al, 2019). In the future, more complex device designs that have additional mixers for on-chip preparation of different FG-Nups may address this question.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that different FG-Nups might stabilize the liquid state when combined together. Analogues for this hypothesis are ubiquitous in the literature, e.g., the inhibition of amyloid-β plaques or aggregates by α-synuclein (Bachhuber et al, 2015) or mixing of the intrinsically disordered protein FUS with EWS or TAF15 (Marrone et al, 2019). In the future, more complex device designs that have additional mixers for on-chip preparation of different FG-Nups may address this question.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our study provides an additional proof of concept that modulating autophagy may be of therapeutic interest in ALS/FTD. Indeed, previous studies have shown that stimulating autophagy is beneficial in SOD1, FUS, and TDP‐43 cell or animal models of ALS (Hetz et al , ; Crippa et al , ; Wang et al , ; Castillo et al , ; Barmada et al , ; Perera et al , ; Marrone et al , , ). In agreement with these works, we found that compounds known to induce autophagy, notably promethazine, are able to bypass the reduced expression of C9ORF72 and can promote the clearance of DPR proteins, thus reducing their toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Promethazine is a sedative and antihistamine drug with antipsychotic effects that belongs to a class of phenothiazine derivatives known to activate autophagy in neuronal cell cultures (Tsvetkov et al , ). Interestingly, these compounds ameliorate neuronal cell dysfunctions and prevent neuronal cell death in SOD1, TDP‐43, and FUS cellular and animal models of ALS (Barmada et al , ; Patten et al , ; Marrone et al , , ). Furthermore, pimozide, a phenothiazine derivative related to promethazine, displayed some promising effects in a short randomized clinical trial of sporadic ALS (Patten et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of autophagy was 286 observed when over-expressing altFUS alone, absent when over-expressing FUS alone (wild-type 287 or ALS-associated R495x mutant) and reconstituted when co-expressing FUS and altFUS. This 288 demonstrates that the inhibition of autophagy, previously described in FUS-linked ALS 11,21 , has 289 been incorrectly associated to the FUS protein. AltFUS inhibits autophagy.…”
mentioning
confidence: 91%
“…The 53 protein is involved in RNA processing, DNA repair and cellular proliferation, although its functions 54 are not precisely elucidated 9 . Most of the mutations associated with neurodegenerative diseases 55 alter FUS NLS [11][12][13] . More recently, mutations in FUS 3'UTR were described in ALS patients and 56 linked to an increased level of FUS mRNA and protein [14][15][16] .…”
mentioning
confidence: 99%